Orodispersible Films: Current Innovations and Emerging Trends - Shery Jacob; Sai H. S. Boddu; Richie Bhandare; Samiullah Shabbir Ahmad; Anroop B. Nair (Pharmaceutics, 2023)
Orodispersible films (ODFs) are thin, mechanically strong, and flexible polymeric films that are designed to dissolve or disintegrate rapidly in the oral cavity for local and/or systemic drug delivery. This review examines various aspects of ODFs and their potential as a drug delivery system. Recent advancements, including the detailed exploration of formulation components, such as polymers and plasticizers, are briefed. The review highlights the versatility of preparation methods, particularly the solvent-casting production process, and novel 3D printing techniques that bring inherent flexibility. Three-dimensional printing technology not only diversifies active compounds but also enables a multilayer approach, effectively segregating incompatible drugs. The integration of nanoparticles into ODF formulations marks a significant breakthrough, thus enhancing the efficiency of oral drug delivery and broadening the scope of the drugs amenable to this route. This review also sheds light on the diverse in vitro evaluation methods utilized to characterize ODFs, ongoing clinical trials, approved marketed products, and recent patents, providing a comprehensive outlook of the evolving landscape of orodispersible drug delivery. Current patient-centric approaches involve developing ODFs with patient-friendly attributes, such as improved taste masking, ease of administration, and enhanced patient compliance, along with the personalization of ODF formulations to meet individual patient needs. Investigating novel functional excipients with the potential to enhance the permeation of high-molecular-weight polar drugs, fragile proteins, and oligonucleotides is crucial for rapid progress in the advancing domain of orodispersible drug delivery.